Variation in Bacterial Community Structure in Rhizosphere and Bulk Soils of Different Halophytes in the Yellow River Delta - Zhao, Yinghan; Li, Tian; Shao, Pengshuai; Sun, Jingkuan; Xu, Wenjing; Zhang, Zehao (Frontiers in Ecology and Evolution, 2022)
Soil microorganisms play the important role in driving biogeochemical cycles. However, it is still unclear on soil microbial community characteristics and microbial driving mechanism in rhizosphere and bulk soils of different halophyte species. In this study, we analyzed bacterial communities in the rhizosphere and bulk soils of three typical halophytes in the Yellow River Delta, i.e., Phragmites communis, Suaeda salsa, and Aeluropus sinensis, by high-throughput sequencing. The contents of total carbon, total nitrogen, and available phosphorus in rhizosphere soils of the three halophytes were significantly higher than those in bulk soils, which suggested a nutrient enrichment effect of the rhizosphere. Rhizosphere soil bacterial α-diversity of P. communis was higher than that in bulk soil, whereas bacterial α-diversity in rhizosphere soil of S. salsa and A. sinensis was lower than those in bulk soil. The dominant bacterial phyla were Proteobacteria, Actinobacteria, Chloroflexi, and Bacteroidetes, which accounted for 31, 20.5, 16.3, and 10.3%, respectively. LDA effect size (LEfSe) analysis showed that the bacterial species with significant differences in expression abundance was obviously different in the rhizosphere and bulk soil of three halophytes. The principal component analysis (PCoA) showed that bacterial community composition was greatly different between rhizosphere and bulk soils of P. communis and S. salsa, while no difference in A. sinensis. Changed bacterial community composition was mainly ascribed to salinity in rhizosphere and bulk soils. Additionally, salinity was positively correlated with Bacteroidetes and negatively correlated with Actinobacteria and Acidobacteria. Our study clarified the variation in bacterial community structure between rhizosphere and bulk soils with soil physicochemical properties, which proved a biological reference to indicate the characteristics of saline and alkaline land.